See You in September - Winlöf, Anders (My University, 2010)
The lack of energy is not a problem. Renewable energy sources can provide our planet’s energy consumption up to 15.000 times. When we choose to fully harness these energy sources new possibilities will rise. This Master Thesis asks: How can we create architecture that is built by energy and what are the advantages? Due to a wave power plant, the project offers facilities for wave surfers in the sand dunes of Kåsa, Varberg. It is designed by premises of the wind, materialized by sand and powered by the waves. Since the surf season in Sweden is limited the facilities only exist during fall & winter. When spring arrives, the power is turned off and the structure cease to exist. That is why my project is called See You in September!
Keywords: Samhällsbyggnadsteknik; Civil Engineering